Fadil Pasha’s Qasida as an Answer to Ziya-Pasha’s Zafernama - Nametak, Fehim (Prilozi za orijentalnu filologiju, 2017)
The most important XIX century Bosnian-Herzegovinian poet in the Turkish language, Fadil-pasha Šerifović (Şerif-zade, 1802-1880), though an old school poet, kept close relations to some modern Turkish poets. Fadil-pasha’s con- tacts with Ziya-pasha (1825-1880) were intensified with Ziya-pasha’s arrival to Bosnia in the capacity of a müfettiş (controller). On that occasion Fadil-pasha praised a commendation qasida to this Turkish official and poet, which is included into the hand-written Divan by Fadil-pasha Šerifović (the handwritings’ fund to the Oriental Institute nb.4520 and Gazi Husrev-bey’s Library R-92 and R-93). Recently, this qasida -commendation was included into the book by M. Kaya Bilgegil: Ziyö-paşa üzerinde bir araştırma, Ankara, 1979. For the fırst time, this work includes a new poem by Fadil-pasha Šerifović, knovvn neither within the scope of the Bosnian-Herzegovinian cultural heri- tage in the Turkish language, nor within the scope of the Turkish literature history. The poem is a satire and contains a harsh disapproval of Ziya-pasha, who signed his famous Zafernama, sent as a critique to Grand Vizier Mehmed Emin Ali-pasha (1815-1871), with the name Fadil-pasha Bosnevi Mevlevi mutesarrif-i İzmit. It is diffıcult to fınd, in Turkish literature alone, not to mention in Bosnian literature in Turkish, a poem with such a harsh critique of a person, occurrence or social movement. By the manner of writing, this poem leaves the scope of the divan poetry, so its author, Fadil-pasha, who ordered copying of his Divan from the Sarajevo calligrapher Muhamed Ševki Imamović, excluded it from Divan. We found the poem in the ample historical work Tarih-i Enveri by Muhamed Enveri Kadić, v. XXVI, p.105.